PEMBERDAYAAN UMKM PEREMPUAN KOTA DENPASAR DIBIDANG E-COMMERCE - Linawati Linawati; N.M.A.E.D. Wirastutia; I.M.O. Widyantara; D.M. Wiharta; P.A. Mertasana (Buletin Udayana Mengabdi, 2018)
Micro, Small, Medium Enterprise (MSME) in Indonesia, especially MSME business women in Denpasar – Balineeds innovation using information communicaton technology to expand their business. Then the enterprise canbe transformed to be e-commerce. Thus, e-commerce workshop has been designet and implemented for MSMEbusiness women in Denpasar City in collaboration with Department of Women and Children empowerment,Denpasar City. From the workshop evaluation results, most of participants were satisfied and theirunderstanding with e-commerce was increased. As a result, the workshop increases their capacity building as aMSME business woman in term of e-commerce. This is shown by their statements that more than 70% of totalparticipant approved the workshop was very effective, and they eager to implement it in their business.